2016
DOI: 10.1001/jamacardio.2016.1325
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Adult Outpatients With Heart Failure and Improved or Recovered Ejection Fraction

Abstract: Outpatients with HFrecEF have a different clinical course than patients with HFpEF and HFrEF, with lower mortality, less frequent hospitalizations, and fewer composite end points. These patients may need to be investigated separately in outcomes studies and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
195
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 27 publications
(19 reference statements)
19
195
5
3
Order By: Relevance
“…18 However, recent studies have shown that the patients with reverse LV remodeling and normalization of LVEF continue to experience heart failure admissions and heart failure deaths. 6, 19 These and other observations in patients supported with left ventricular assist devices have highlighted the importance of the differences between myocardial recovery, wherein patients remain free from future heart failure events, versus myocardial remission that is characterized by reverse LV remodeling and improved LVEF with recurrent heart failure admissions. 10 Basuray and colleagues have shown that patients with a recovered LVEF >50% continue to experience heart failure admissions and heart failure deaths, suggesting that patients with a recovered LVEF represent a group of patients who have a milder, but persistent heart failure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, recent studies have shown that the patients with reverse LV remodeling and normalization of LVEF continue to experience heart failure admissions and heart failure deaths. 6, 19 These and other observations in patients supported with left ventricular assist devices have highlighted the importance of the differences between myocardial recovery, wherein patients remain free from future heart failure events, versus myocardial remission that is characterized by reverse LV remodeling and improved LVEF with recurrent heart failure admissions. 10 Basuray and colleagues have shown that patients with a recovered LVEF >50% continue to experience heart failure admissions and heart failure deaths, suggesting that patients with a recovered LVEF represent a group of patients who have a milder, but persistent heart failure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Also nearly half of allo patients increased EF to levels above 40% (Figure 3), an accepted cut-off for the diagnosis of NIDCM (1,18). HF with recovered EF is a recognized syndrome that carries an improved prognosis relative to HF with persistently low EF (19). As such, if the present results are replicated in a larger trial, they represent a major clinical advance for NIDCM, a condition affecting individuals of all ages and accounting for approximately half of the heart transplants (2,20).…”
Section: Discussionmentioning
confidence: 99%
“…We found that PI-based regimens were associated with an increase in CV mortality among PHIV with HF. The mechanism for this increase in CV mortality related to PI use is unclear, but several possibilities exist, including the following: 1) patients prescribed PIs had an increased 30-day HF readmission rate, which is closely linked to mortality in broad groups of patients with HF (23);2) patients receiving ART had a higher PASP and a lower LVEF, both strong predictors of adverse outcomes, including mortality, in HF (24,25); and 3) PHIV with HF who were taking a PI had increased rates of diabetes and CAD, both independent risk factors for mortality in HF (26,27). Additionally, other factors not addressed in this study may have played a role.…”
Section: Discussionmentioning
confidence: 99%